Auteur Song as a Meeting Ground between "Art" and "Popular" Cultures (with Critical Notes on a Few Tendencies in Popular Musicology) - La Via, Stefano (Analitica. Rivista online di studi musicali, 2016)
The study of the relationhips between verbal language and musical expression, if applied to the most various historical and cultural contexts, facilitates a critical-analytical and interdisciplinary-transversal approach, capable of seriously challenging the traditional dichotomy “art”/“popular” cultures (colto/popolare), as well as the most recent tendency – especially in Italy – to give different meanings to analogous terms such as popolare and popular. Such a transcultural approach emphasizes not only divergences, especially in terms of compositional technique and textual transmission, but also no less relevant concordances, concerning the basic principles of music-word interaction. The vast realm of modern auteur song (canzone d’autore), perhaps more than any other, represents the ideal space of meeting and interchange – hardly reducible to the category of popular – between heterogeneous but not at all incompatible traditions and experiences. It is precisely in such an open interspace that the most diverse “art” and “popular” literary-musical practices have always naturally encountered one another in a dialogue that tends to knock down persistent, ideological barriers. The present essay argues this basic thesis on the ground of historical considerations and synthetic exemplifications, with reference to some of the most representative international repertoires (French chanson, Italian canzone, Brasilian canção, British and North-American song).